Effect on climatic factor towards population of bagworm at Felda Trolak oil palm plantation / Muhammad Fauzan Mahleh - Mahleh, Muhammad Fauzan (Faculty of Plantation and Agrotechnology, 2018)
Oil palm (Elaeis guineensis) is known to be one of the important crops that contribute on developing the economic sectors in Malaysia. As the productions of Fresh Fruit Bunches (FFB) are influenced by the number of fronds that exists on the oil palm tree. The main problem of the reduction of productivity rate has become serious due to the leaf-eating pest which is known as bagworm (Metisa plana). The objectives of this study is to study the effect of climatic factor towards population of bagworm in oil palm plantation. The site selection for our study is conduct at Felda Trolak. Method that been used is systematic sampling to collect bagworm population data, and for amount of rainfall (mm) and temperature are collected uses rain gauge and temperature devices. An “IBM SPSS Statistic 22” is employed to analyses the relationship between climatic factor and population of bagworm by using correlation modelling. The graph result for the relationship between bagworm population and the temperature show that when the temperature is increase the amount of bagworm also increase and have strong positive correlation. The graph result for the relationship between bagworm population with the amount of rainfall show that when the amount of rainfall is low the amount of bagworm will increase and have a strong negative correlation.